A FEMINIST REFLECTIVE ANALYSIS OF GENDER MAINSTREAMING IN YOUTH POLICY AND PRACTICE IN THE REPUBLIC OF MOLDOVA - KELLUM, Jane (Economy and Sociology, 2021)
This year, 2020, marks the 25th anniversary of the 1995 United Nations Fourth World Conference on Women in Beijing where gender mainstreaming was introduced. Since then, gender mainstreaming has come to be recognized as the inter-governmentally agreed strategy to achieve gender equality and female empowerment and involves integrating a gender perspective into all aspects of governmental policy, regulation, and budgeting, with an eye towards promoting equality between women and men, social inclusion, and eliminating discrimination in all its forms. Despite notable achievements, an important body of feminist scholarship reveals that gender mainstreaming faces many challenges. In this paper, I contribute to this body of knowledge by using a feminist reflective practice approach to analyze the gender mainstreaming process I undertook as part of the 2020 Comprehensive Youth Sector Analysis in the Republic of Moldova. Through this analysis, I identify a number of challenges that can be understood as part of the larger social construction of gender inequality and conclude that gender mainstreaming processes embody the same gender inequality and patriarchy that we encounter in our larger social structures. This, in turn, acts as one of the greatest threats to gender mainstreaming as an effective strategy to achieve gender equality.